INTERPRETASI POLITIK TEMPATAN DALAM UNGKAPAN “ADUHAI MALANGNYA PAK KADUK, AYAMNYA MENANG KAMPUNG TERGADAI”: ANALISIS PRAGMATIK - Muhammad Zaid, Daud; Mary Fatimah, Subet; Awang Azman, Awang Pawi (Universiti Sultan Zainal Abidin, 2023)
This study aims to analyse Pak Kaduk’s seloka line “Aduhai malangnya Pak Kaduk, ayamnya menang kampung tergadai” in local politics scenario. The data of this study is a Malay classical poetry known as seloka Pak Kaduk which is obtained from an anthology entitled “Lukisan Zaman”. To further complement of the research, data was also taken from Facebook search engine which is confined to current issues related to local politics. To relate the data of this study, the researchers used a pragmatic approach: Relevance Theory by Sperber and Wilson (1986). The research found that, there are manifestations of criticisms of this line such as, “criticism of the attitude of someone who makes reckless decisions”, “criticism of a person who does not think about the decisions he make will cause others to suffer” and the “criticism of superiors using power or trickery to deceive subordinates”. In conclusion, the manifestation of criticisms of this line of seloka does not end at surface level only, but the meaning can be expanded in the current political context as well. It is hoped that this study can make the valuable oral literature of our ancestors as further reference in discussing the current local political situation as history proved that the history of a nation can as well be referred further by perusing the classical literature’ work.